Therapeutic management of carbamazepine's complications in front of essential trigeminal neuralgia - B. Zaher; S. Bouzoubaa; I. Ben Yahya (Advances in Oral and Maxillofacial Surgery, 2022)
The aim of this work is to know how to manage the complications of carbamazepine prescription following an essential trigeminal neuralgia (ETN). Essential trigeminal neuralgia is a syndrome of unilateral, paroxysmal, stabbing facial pain, originating from the trigeminal nerve. The age of onset is usually between 40 and 60 years, most often in females with a global incidence of approximately 4–28.9 per 100,000 individuals. Many medical and surgical treatments are available. Most patients respond well to pharmacotherapy; carbamazepine and oxcarbazepine are first line therapy, while lamotrigine and baclofen are considered second line treatments. Other drugs such as gabapentin, pregabalin, and botulinum toxin-A are alternative treatments. Surgical interventions are reserved for patients who do not respond to adequate medical therapy. This work reports the case of a patient who was diagnosed with an ETN of the mandibular nerve (V3) and in whom carbamazepine was prescribed. A month and a half after the start of treatment, the patient presented with severe cutaneous-mucosal symptoms, which allowed us to evoke Stevens-Johnson syndrome as a complication to carbamazepine treatment.